2017
DOI: 10.1186/s12940-017-0311-8
|View full text |Cite
|
Sign up to set email alerts
|

Hazardous waste and health impact: a systematic review of the scientific literature

Abstract: Waste is part of the agenda of the European Environment and Health Process and included among the topics of the Sixth Ministerial Conference on Environment and Health. Disposal and management of hazardous waste are worldwide challenges. We performed a systematic review to evaluate the evidence of the health impact of hazardous waste exposure, applying transparent and a priori defined methods. The following five steps, based on pre-defined systematic criteria, were applied. 1. Specify the research question, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(80 citation statements)
references
References 86 publications
(61 reference statements)
0
72
0
8
Order By: Relevance
“…Some studies in Brazil and in other countries found some similar results that most of the waste collectors were women, with over 30 years old and low level of education. They had few job options other than waste picking due to their high illiteracy and low education level [1] , [20] – [23] .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies in Brazil and in other countries found some similar results that most of the waste collectors were women, with over 30 years old and low level of education. They had few job options other than waste picking due to their high illiteracy and low education level [1] , [20] – [23] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ineffective hazardous waste management (HWM) is detrimental to the environment and human health due to exposure of these toxic ingredients. A review by Fazzo et al lists several investigations, that indicate poor and illegal waste management as the most important world-wide cause of soil and groundwater contamination [4]. Source reduction and efficient HWM are essential to address the potential hazards of HW (particularly those resulting from improperly identified, treated, recycled, stored, transported, and disposed HW) to human health and the environment [5].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental contamination from industrial activity presents a significant risk to urban public health (Fazzo, Minichilli & Santoro et al, 2017). An estimated 61 million people worldwide are affected by heavy metals and toxic chemicals from contaminated sites (Landrigan et al, 2017), with exposure being responsible for the ill health of hundreds of thousands of people (Landrigan, Fuller, & Horton, 2015).…”
Section: Introductionmentioning
confidence: 99%